ANALISIS KEPUASAN KONSUMEN DENGAN ALGORITMA C4.5 PADA UMKM MINIMALL - wazir, indra; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2021)
MiniMall MSMEs is a business that is engaged in the sale of products, including: glassware, clothing, household items, accessories for fashion and electronic equipment in the city of Batam. MiniMall MSMEs take advantage of the e-commerce platform to sell their products. Based on product sales data from March 2020 to February 2021, there was a decrease in the level of sales and this condition is now a problem for MiniMall MSMEs because it can interfere with the continuity of its business. Seeing these problems, the authors want to analyze the consumer satisfaction of the MiniMall MSMEs because the level of product sales is basically related to customer satisfaction. The implementation of the analysis in the study was carried out using data mining techniques with the C4.5 algorithm. The analysis was carried out by performing manual calculations using the gain and entropy formula of the C4.5 algorithm and using the WEKA version 3.9.5 application to ensure the correctness and accuracy of the manual calculations. It is concluded that the customer satisfaction of the MiniMall MSMEs is proven to be analyzed using data mining with the algorithm from C4.5 and the results of the research can be used to help increase product sales. In addition, the decision tree and the results of calculations manually using the gain and entropy formula of the C4.5 algorithm have the same results as data testing using the WEKA application version 3.9.5, so it can be said that the results of research through the use of the WEKA application and manual calculations are the same. correct and accurate, making it easier for researchers when analyzing customer satisfaction data derived from questionnaires. The results showed that the indicators of product availability, product quality and delivery accuracy significantly affected consumer satisfaction of the MiniMall MSMEs.